Autophagy: an essential but limited cellular process for timely skeletal muscle recovery from injury. Issue 7 (2nd July 2020) - Call, Jarrod A.; Nichenko, Anna S.
ABSTRACT: Macroautophagy/autophagy induction, i.e., the formation of autophagosomes, is robust following many forms of muscle injury. Autophagy inhibition studies strongly indicate that autophagy is necessary for successful muscle fiber recovery. Now, there are accumulating pieces of evidence indicating that autophagosome clearance, i.e., autophagy flux, does not increase to match the burden of accumulating damaged proteins and organelles after muscle fiber damage, creating a bottleneck effect. Some potential consequences of the bottleneck effect are reduced regenerative capacity marked by the inadequate activation of muscle stem cells (i.e., satellite cells) and a lesser commitment toward differentiation due to a deficiency in energetic substrates and/or molecular signaling pathways. These findings highlight an emerging area of investigation for both autophagy and muscle regeneration fields. The identification of the molecular mechanisms governing autophagy and autophagy flux may serve as targets for future therapies to enhance the recovery of its function in healthy and diseased muscle. Abbreviations: BNIP3: BCL2/adenovirus E1B interacting protein 3; CQ: chloroquine; DMD: Duchenne muscular dystrophy; MAP1LC3/LC3: microtubule-associated protein 1 light chain 3; ULK1: unc-51 like kinase 1.